2021
DOI: 10.5210/spir.v2021i0.12137
|View full text |Cite
|
Sign up to set email alerts
|

The Case Act: Implications for Internet Studies Research

Abstract: Copyright policy is inextricably entangled with the work of academic researchers on Internet culture. This paper examines a new U.S. law, the CASE Act, which creates a new venue for resolving copyright disputes for up to $30,000. We discuss the implications of such a venue for U.S.-based internet studies research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There has been a general assumption that older people and young people consume and perceive information/media content differently (Aufderheide et al, 2015), and the Virtua (2022) report also identified many areas where Gen Z and older people had different behaviors and perceptions regarding digital items. This study, however, did not find many relations between age and e-book ownership perceptions.…”
Section: About the Generational Gapsmentioning
confidence: 99%
“…There has been a general assumption that older people and young people consume and perceive information/media content differently (Aufderheide et al, 2015), and the Virtua (2022) report also identified many areas where Gen Z and older people had different behaviors and perceptions regarding digital items. This study, however, did not find many relations between age and e-book ownership perceptions.…”
Section: About the Generational Gapsmentioning
confidence: 99%